Trainee Teachers Level of Willingness for Inclusive Education - Nancy Anthony; Mohd Hanafi Mohd Yasin (Department of Special Education, 2019)
Every student at the Teacher Education Institute (IPG) has now been given an inclusive education course so they know about its implementation at school. Therefore, this research looks at how far the willingness of new teachers to be placed in schools with inclusive education. It was conducted in IPG in Sabah which involved 50 trainees from 5 different courses and took the Inclusive Education subject. It is a survey of quantitative reviews and uses questionnaires for data collection. The data were analyzed using Statistical Packages for the Social Science (SPSS) to see the frequencies, percentage and mean descriptive analysis. Besides, five trainee teachers from five different courses were interviewed to identify barriers that may interfere with the trainee teachers’ willingness for inclusive education. The results showed that 86 % of the trainee teachers are ready to accept special need students without prejudice and 84 % are willing to approach and recognize special needs students in their classroom. The findings also showed that there was no significant difference in the readiness of the IPG trainee in the implementation of inclusive education based on gender namely t = -0.270 with P = 0.811 greater than 0.05 (P <0.05). The trainee teachers should be able to meet the needs of students with disabilities in school. The success of inclusive education rests on teacher preparation gearing towards inclusive education. However, continuous guidance is essential to help produce qualified teachers, especially in understanding the underlying philosophy of inclusive education.